ALCAT1 Overexpression Affects Supercomplex Formation and Increases ROS in Respiring Mitochondria - Rieger, Bettina; Krajčová, Adéla; Duwe, Patrick; Busch, Karin B (Oxidative medicine and cellular longevity, 2019)
Cardiolipin (CL) is a multifunctional dimeric phospholipid that physically interacts with electron transport chain complexes I, III, and IV, and ATP synthase (complex V). The enzyme ALCAT1 catalyzes the conversion of cardiolipin by incorporating polyunsaturated fatty acids into cardiolipin. The resulting CL species are said to be more susceptible to oxidative damage. This is thought to negatively affect the interaction of cardiolipin and electron transport chain complexes, leading to increased ROS production and mitochondrial dysfunction. Furthermore, it is discussed that ALCAT1 itself is upregulated due to oxidative stress. Here, we investigated the effects of overexpression of ALCAT1 under different metabolic conditions. ALCAT1 is located at the ER and mitochondria, probably at contact sites. We found that respiration stimulated by galactose supply promoted supercomplex assembly but also led to increased mitochondrial ROS levels. Endogeneous ALCAT1 protein expression levels showed a fairly high variability. Artificially induced ALCAT1 overexpression reduced supercomplex formation, further promoted ROS production, and prevented upregulation of coupled respiration. Taken together, our data suggest that the amount of the CL conversion enzyme ALCAT1 is critical for coupling mitochondrial respiration and metabolic plasticity.
Keywords: Reactive Oxygen Species; Cardiolipins; Galactose; lidé; Humans; multimerizace proteinu; galaktosa; membránový potenciál mitochondrií; Cell Respiration; multiproteinové komplexy; buněčné dýchání; mitochondrie; HeLa buňky; kardiolipiny; HeLa Cells; reaktivní formy kyslíku; Multiprotein Complexes; 1-acylglycerol-3-fosfát-O-acyltransferasa; Oxidative Stress; oxidační stres; Mitochondria; Membrane Potential, Mitochondrial; 1-Acylglycerol-3-Phosphate O-Acyltransferase; Protein Multimerization